If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + 4x + 3 + 7 = 9x + 3 + 4x Reorder the terms: 3 + 7 + 10x + 4x = 9x + 3 + 4x Combine like terms: 3 + 7 = 10 10 + 10x + 4x = 9x + 3 + 4x Combine like terms: 10x + 4x = 14x 10 + 14x = 9x + 3 + 4x Reorder the terms: 10 + 14x = 3 + 9x + 4x Combine like terms: 9x + 4x = 13x 10 + 14x = 3 + 13x Solving 10 + 14x = 3 + 13x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13x' to each side of the equation. 10 + 14x + -13x = 3 + 13x + -13x Combine like terms: 14x + -13x = 1x 10 + 1x = 3 + 13x + -13x Combine like terms: 13x + -13x = 0 10 + 1x = 3 + 0 10 + 1x = 3 Add '-10' to each side of the equation. 10 + -10 + 1x = 3 + -10 Combine like terms: 10 + -10 = 0 0 + 1x = 3 + -10 1x = 3 + -10 Combine like terms: 3 + -10 = -7 1x = -7 Divide each side by '1'. x = -7 Simplifying x = -7
| 18=3d | | 8=(10)w(2) | | ln(y)=2ln(x)+ln(10) | | 23x+21x=72 | | h-23=27 | | 9i*12i= | | 2(x+1)+5=-4(x-2) | | 5(3x+7)=-19+39 | | 17+p=30 | | 4+5lnx=19 | | 5u^3+4u^2-25u-20=0 | | 5(5x+2)-5= | | 4(-6x-2)+10=8(-3x-1)+14 | | n/-20=0 | | -4(15y+1)+8=20(-3y+5)-102 | | -344=8(8v-3) | | (X^3-7)/(x-2) | | 18x=288 | | 1(-4x-5)+7=4(-1x-4)+18 | | x+5=8+x | | s^2=323 | | 3+3x=3x+2 | | 3/4(2?3M)=24 | | 26/y=2 | | -147=3k-3(8k+7) | | -1(x+3)-3=-6(x+8) | | 5(x/5)-3(5)=5(x/5) | | 10=-7-3x | | -6z-9(-8z-4)=2-5(-9-z) | | 5(1-2x)+8=15 | | 6(x-3)-2(x-2)=1 | | 23=33-2(4-2w) |